Antagonistic Fish Gut Bacterium Lactobacillus sp. as Biocontrol Agent in Ornamental Fish Culture - T., Jawahar Abraham (Fishery Technology, 2025)
The effect of addition of a fish gut bacterium Lactobacillus sp. P21 in to the rearing water on Pseudomonas fluorescens induced mortalities in ornamental fishes was examined. The goldfish, Carassius auratus and swordtail, Xiphophorus helleri were almost 3.7-4.7 times as likely to become infected when exposed to P. fluorescens (106 cfu/mL) compared to control. The introduction of Lactobacillus sp. into the culture system seeded with P. fluorescens reduced the relative risk by more than two folds through the production of low molecular weight bacteriocin-like-substance.